Nonresponse trends in establishment panel surveys: Findings from the 2001-2017 IAB establishment panel - Corinna König; Joseph W. Sakshaug (Journal for Labour Market Research, 2023)
Many household panel surveys have experienced decreasing response rates and increasing risk of nonresponse bias in recent decades, but trends in response rates and nonresponse bias in business or establishment panel surveys are largely understudied. This article examines both panel response rates and nonresponse bias in one of the largest and longest-running establishment panels, the IAB Establishment Panel. Response rate trends are reported over a 17-year period for each annual cohort and rich administrative data are used to evaluate changes in nonresponse bias and test hypotheses regarding short-term and long-term panel participation. The findings show that while cumulative panel response rates have declined over time, wave-to-wave reinterview rates have remained largely stable. Reinterview nonresponse bias has also remained stable, while cumulative nonresponse bias has consistently increased within all cohorts. Larger establishments and those that experienced an interviewer change or did not answer all survey questions (item nonresponse) in a previous wave were less likely to continue participating in the panel. These findings and their practical implications are discussed in conclusion.
Keywords: C12; C83; 330; Administrative data; Attrition; Establishment survey; Nonresponse bias; Panel participation; Paradata